Wind Tunnel Test of Counter‐Rotating Dual Rotor Wind Turbine With Double Rotational Armature Design - Niels Adema; Wouter Swart Ranshuysen; Arjen deRuijter; Gerard Schepers (Wind Energy)
ABSTRACT This study evaluates the performance of a counter‐rotating dual rotor wind turbine (CR‐DRWT) with 2 m2 rotor radius equipped with a double rotational armature in an open jet wind tunnel. With only one similar‐sized design previously assessed in a wind tunnel, this study offers valuable validation material for the literature. Through wind tunnel testing, the CR‐DRWT confirmed earlier findings in literature and achieved a 15% to 50% increase in power output and a 10% increase in efficiency (CP) compared to a single rotor configuration at higher wind speeds (> 7 m/s). Though these gains were not observed at lower wind speeds (4–7 m/s). The simplified mechanics of a double rotational armature show promise for SWTs, as financial viability depends on reducing LCOE through efficiency improvements that maximize energy capture. The design's maximum CP values were below those achieved in previous field tests at larger scale highlighting potential for improvement for smaller sized turbines. To further explore the aerodynamics of CR‐DRWT's, computational fluid dynamics (CFD) simulations are recommended, as they could provide insights into optimizing flow dynamics around CR‐DRWT's. Finally, the study emphasizes the need for precise pitch angle and rotational speed measurements to improve the value of future measurements.